Around the world in 80 musical instruments - Dickmann, Nancy; Downing, Sue, 1964- (London : Welbeck Editions, 2022)
Presents a visual celebration of the musical instruments found across the world, and how they are related to one another.
Includes foldout pages.
Includes index.
4.7
K-3.
K-3
english
Keywords: Musical instruments -- Juvenile literature; Musical instruments; Musical instruments